In vitro cytotoxic activity of aqueous extract of Delonix elata (L.) gamble (fabaceae) leaves on mcf-7 & hep g-2 cell lines - Kola, Phani Kumar; K, Shyam Prasad; N, Lakshmi Sudeepthi; D, R.CH.Sekhara Reddy; Sk, Abdul Rahaman; P, Madan Ranjith (International Journal of Pharmacology and Toxicology, 2014)
To investigate, in vitro cytotoxic effect of aqueous extract of Delonix elata leaves belongs to family Fabaceae. The dried Delonix elata leaf extract was used to determine the qualitative preliminary phytochemical analysis and in vitro cytotoxic assay against breast cancer (MCF-7) & Hepatic cancer (HepG2) cells by using MTT assay method. Phytochemical evaluation revealed the presence of flavonoids, tannins, phenolic compounds, steroids and saponins and this result was supported by IR data, which exhibits anticancer activity against breast and hepatic cancer cell lines. So the current investigation showed that Delonix elata leaf extract possesses the dose dependent cytotoxic activity against breast and hepatic cancer cell lines. Keywords: Delonix elata, Aqueous Extract, Flavonids, MCF-7 & Hep G2 Cell Line.